Postgraduate Research Engagement in Low Resource Settings - Atibuni, Dennis Zami; Ssempala, Fredrick; Lam, James Lagoro; Orluwene, Goodness Wobihiele; Ajala, Ibrahim; Sekiwu, Denis; Ocan, Johnson; Mayengo, Nathaniel; Olema, David Kani; Kibanja, Grace Milly; Ssenyonga, Joseph; Ndlovu, Sibonokuhle; et al. (IGI Global, 2020)
For any country to develop, it should be able to conduct research to generate knowledge necessary to solve problems of humanity by producing necessary goods and services. Research is essential for any nation’s success. Most goods and services consumed today are products of research conducted in developed countries by post-graduate students. Unfortunately, most post-graduate students in developing countries face a lot of challenges that limit their ability to engage in original research that should be published in refereed journals and to acquire necessary patents accordingly. Curriculum gaps inhibit most graduate students in low-resource settings from engaging in productive research necessary to transform the developing country’s economy. Hence, the chapter discusses the importance of research engagement and strategies to fill curriculum gaps in the postgraduate programs to enhance research engagement among the post-graduate students in low-resource settings
Keywords: Curriculum; System Thinking; Curriculum Gap; Research Engagement